Dislocation density-based simulation of pre-mixed jet effects on residual stress and cell size in 18CrNiMo7-6 alloy steel - MingHao Zhao; HaiYang Hou; FeiHu Ren; Chunsheng Lu; JianWei Zhang; BingBing Wang (Journal of Materials Research and Technology)
In this paper, a finite element model is developed to investigate residual stress and microstructural changes in 18CrNiMo7-6 alloy steel during pre-mixed jet strengthening. The model employs a dislocation density-based constitutive relationship, with parameters optimized via a genetic algorithm. A fully coupled stress integration algorithm ensures the numerical stability. The model is validated by experiments, with a maximum error of 2.6% in predicting residual stress. It is shown that the dislocation cell sizes measured from experiments are consistent with that obtained by simulations. As the peening intensity increases, the maximum residual stress, the depth of a residual stress layer, and the thickness of a compressive residual stress layer gradually increase. The rise in residual stress is accompanied by formation of dislocation proliferation and refined microstructural layers. Additionally, the depth of a refined layer increases with a higher pre-mixed jet intensity. While the coverage increase has a minimal impact on the smallest average dislocation cell size, larger shot diameters lead to smaller dislocation cell sizes.